Inoculação de Azospirillum brasilense no incremento ao crescimento e produção de hastes de rosa - Silva, Giordana Menegazzo da (2021)
The rose bush is the cut flower must consumed worldwide, and it is increasingly necessary to use technologies that improve its quality to then obtain a consolidated space in the Market, which is increasingly more competitive. Inoculation of Azospirillum in rosebush can assist in rooting and absorption of nutrients. Given the above, the objective was to evaluate an inoculation of Azospirillum brasilense on rose seedlings in order to favor the growth and production of stems, under conditions of protected environment. Two experiments were carried out at the Unioeste Protected Cultivation Station, with a randomized block design, in a factorial scheme. In the experiment, the four options of A. brasilense and three rose cultivars (Tineke, Vegas and Ambiance) were chosen, with three replications and two plants per repetition; and in experiment II, three forms of application of A. brasilense (control treatment, leaf spray, inoculation of the product in the soil) and the three cultivars of rose bush, with four replications and one plant of the microorganism, were tested: fresh biomass from floral rush (g), number of leaves, average length of flower stems (cm), average transverse (cm) and longitudinal (mm) diameter of flower buds and the number of flower stems. In experiment 1, the inoculation of A. brasilense did not show promising results of increased growth and production of rose stems, leading to a decline in the number of flower stems per plant. The results were limited in isolation to the rose cultivars, not being able to attribute the inoculation of the bacterium as a factor that differentiated the results, in view of the existing genetic difference between ‘Tineke’, ‘Vegas’ and ‘Ambiance’. For experiment 2, leaf spraying is superior to treatments in most of the selected parameters, and inoculation of A. brasilense via leaf spraying is indicated.